In Vitro Antifungal and Antivirulence Activities of Biologically Synthesized Ethanolic Extract of Propolis-Loaded PLGA Nanoparticles against Candida albicans. (30th November 2019) - Iadnut, Anupon; Mamoon, Ketsaya; Thammasit, Patcharin; Pawichai, Sudjai; Tima, Singkome; Preechasuth, Kanya; Kaewkod, Thida; Tragoolpua, Yingmanee; Tragoolpua, Khajornsak
Abstract : Propolis is a natural substance and consists of bioactive compounds, which gives it antioxidant and antimicrobial properties. However, the use of propolis is limited by the low solubility in aqueous solutions. Thus, nanoparticles may be likely to accomplish enhanced delivery of poorly water-soluble phytomedicine. The aim of the present study was to fabricate and evaluate the biological activity of ethanolic extract of propolis-loaded poly(lactic-co-glycolic acid) nanoparticles (EEP-NPs). The EEP-NPs were prepared using the oil-in-water (o/w) single-emulsion solvent evaporation technique. The physicochemical properties of EEP-NPs were characterized and tested on their cytotoxicity, antifungal activity, and impact on key virulence factors that contribute to pathogenesis of C. albicans. EEP-NPs were successfully synthesized and demonstrated higher antifungal activity than EEP in free form. Moreover, EEP-NPs exhibited less cytotoxicity on Vero cells and suppressed the virulence factors of C. albicans, including adhesion, hyphal germination, biofilm formation, and invasion. Importantly, EEP-NPs exhibited a statistical decrease in the expression of hyphal adhesion-related genes, ALS3 and HWP1, of C. albicans . The results of this study revealed that EEP-NPs mediates a potent anticandidal activity and key virulence factors by reducing the gene-encoding virulence-associated hyphal- adhesion proteins of C. albicans and, thereby, disrupting the morphologic presence and attenuating their virulence.